Modeling of type-II quantum dot intermediate band solar cells accounting for thermal and optical intersubband transitions - Khalili, Arastoo; Cappelluti, Federica (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
Novel solar cell concepts relying on the use of nanostructures requires ad hoc device modeling tools able to cope with carrier transport and charge transfer mechanisms involving the host bulk material and the quantum confined states. In this work we apply such approach to study the implication of intersubband competitive processes in type-II GaSb/GaAs quantum dots on their application to intermediate band solar cells.